2018
DOI: 10.3390/nano8080600
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Conversion of ZnO/Ni3ZnC0.7/CNT Composite from NiZn Bimetallic MOF Precursor with Enhanced Electromagnetic Property

Abstract: ZnO/Ni3ZnC0.7/x% CNT (x = 0, 2, 5, 10) urchin-like structures have been synthesized using a facile method based on metal-organic frameworks (MOFs) and applied as the electromagnetic absorber. The results of the experiments demonstrate that the content of multi-wall carbon nanotubes (MWCNT) has a great influence on the absorbing performance of the hybrid material. Conduction loss, interfacial polarization and ferromagnetic resonance all contribute to the electromagnetic absorption. The urchin-like ZnO/Ni3ZnC0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Moreover, even if assuming the emission was from interfacial defects, such interfacial defects could also lead to a preferential channeling of the energetic electrons to reach the MOF component of the hybrid structure, enhancing the separation efficiency of photoinduced charge carriers. [ 22 ] Meanwhile, as for the 3D nanostructure of ZnO/Zn‐MOF/CdS, the covalent interaction between ZnO and CdS was enhanced by the in situ growth of Zn‐MOF. [ 20 ] Thus, the direct surface recombination of electron–hole pairs was suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, even if assuming the emission was from interfacial defects, such interfacial defects could also lead to a preferential channeling of the energetic electrons to reach the MOF component of the hybrid structure, enhancing the separation efficiency of photoinduced charge carriers. [ 22 ] Meanwhile, as for the 3D nanostructure of ZnO/Zn‐MOF/CdS, the covalent interaction between ZnO and CdS was enhanced by the in situ growth of Zn‐MOF. [ 20 ] Thus, the direct surface recombination of electron–hole pairs was suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…These defects could be regarded as dipoles for the conversion of electromagnetic energy into thermal energy due to the orientational relaxation process excited by the alternating electromagnetic field. 49 Meanwhile, under the alternating electromagnetic field, the electrons gained sufficient energy transfer and accumulate on the heterointerface. A large number of accumulated space charges would undergo Debye relaxation processes, to achieve the purpose of attenuating incident electromagnetic waves.…”
Section: Acs Appliedmentioning
confidence: 99%
“…[ 167 ] In addition, the multiple scattering and reflection of electromagnetic waves in carbon nanotubes also improve the microwave absorption properties of the material. For instance, Huang et al [ 168 ] synthesized an urchin‐like ZnO/Ni 3 ZnC 0.7 /CNT composite by a facile thermal decomposition based on Ni‐Zn‐MOFs. The experimental results showed that the chemical states of the components and the microwave absorption properties of the hybrid materials can be adjusted by changing the content of multiwall carbon nanotubes (MWCNT).…”
Section: Mofs Derived Carbon‐based Composite Microwave Absorption Mat...mentioning
confidence: 99%